Pengaruh Siklus Hidup Perusahaan Terhadap Konservatisme Akuntansi - Yonia Efrilita; Salma Taqwa (Universitas Negeri Padang, 2019)
This study aims to analyze the effect of the company's life cycle that covers the stage of start-up, growth, and mature to accounting conservatism. Population in this study are manufacturing companies listed in Indonesia Stock Exchange(IDX) in 2013 to2017 period. The sample of study was determined by using purposive sampling method, and that total sample 54 manufacturing companies. In this study, conservatism was measured using accrual earnings measure. The life cycle of companies is measured using cash flow patterns. The data used is secondary data obtained from www.idx.co.id. The analytical method used is the panel regression analysis with Eviews 8 software. The results showed of this study indicate that the life cycle of the company at the start-up stage and growth stage has negative effect on accounting conservatism. The life cycle at mature stage has a positive effect on accounting conservatism.